Effects of different doses of Ganoderic Acid A on nociceptive behaviour and inflammatory parameters in polyarthritic mice rheumatoid arthritis model - Derya Guzel Erdogan; Ayşenur Demır; Hüseyin Baylan; Özcan Budak; Erdem Cokluk; Pelin Tanyerı (Scientific Reports)
Abstract The frequency of autoimmune diseases such as rheumatoid arthritis is increasing annually. Current treatments for these diseases cause new problems due to their side effects. In this study, we investigated the impact of Ganoderic Acid A (GAA), a potent anti-inflammatory herbal molecule, to evaluate the potential efficacy of GAA in alleviating Rheumatoid arthritis (RA)-associated clinical and histopathological manifestations. 40 Balb/c male mice were randomly divided into five groups (n = mice number per each group) as control (C), acetic acid (AA), rheumatoid arthritis (RA), low dose GAA (LGA) and high dose GAA (HGA) groups. Collagen emulsion was applied intra-articularly (ia), and complete Freund’s adjuvant (CFA) was applied subcutaneously (sc) to the RA and GA groups to induce an experimental model of rheumatoid arthritis. Other groups were given physiologic saline (PS) or AA at the same dose and in the same way. The procedures were repeated on the 22nd day; however, incomplete Freund’s adjuvant was applied to the RA and GA groups instead of CFA. PS was given to groups C, AA and RA for 9 days starting from the 22nd day; GAA was applied to the LGA (20 mg/kg) and HGA (40 mg/kg) groups by gavage. We evaluated body weight, arthritis score, knee temperature, knee circumference, behavioural assessment of pain, gait, tail-flick test, hot plate test, locomotor activity test, lower extremity index, spectrophotometric and histopathological evaluation methods, respectively. Compared to the RA group, the clinical arthritis score was reduced in the HGA group (p < 0.05). GAA significantly reduced knee temperatures and knee circumference, with changes in hot plate scores and tail flip test response. In the GAA groups, serum concentrations of AST, IL-6, TNF-α, NFkB were reduced, and joint damage and arthritis scores were also reduced histologically (p < 0.05). The results of this study suggest that the arthritis regressed with GAA treatment. Edema and inflammation were found to be reduced in the GAA groups compared with the RA group. GAA treatment resulted in significant improvements in behavioural activity, reduced inflammation and the damage to cartilage and bone structure and had an antinociceptive effect.